Quelles sont les limites de normalité du LIPOXmax? Peut-on le prédire sans effectuer de calorimétrie d`effort? - Brun, J. F.; Halbeher, C.; Fédou, C.; Mercier, J. (Science & Sports, 2011)
Aim: Exercise calorimetry (EXCAL) allows to target physical activity at the level of the LIPOXmax, a level of heart rate and power at which lipid oxidation is maximal. We aimed at determining: (a) whether one can "predict" the LIPOXmax without performing an exercise test, based solely on power, heart rate and theoretical VO2max data (Pmaxth, FCmaxth and VO2 maxth)? (b) what is the range of normal values of these EXCAL parameters? Patients and results: Seven hundred and fifty-nine patients completed an EXCAL consisting of four steady state bouts of 6 minutes duration, with determination of the LIPOXmax and the crossover point (PCX). Lipid oxidation measured at the LIPOXmax ranges between 38 and 1073 mg/min (median 189; limit of the lowest quartile (Linf25): 140 mg/min). The LIPOXmax occurs between 3.6 and 101.5 % of theoretical Pmax (median 29 %; Linf25: 22 %), or 64.01 ± 0.52 % of the FCmaxth (Linf25: 58 %) or 29 % of the FC reserve. Targeting at the level of these theoretical values ±5 % will correspond to the actual LIPOXmax in 30-40 % of the cases, meaning that 60-70 % of patients are not trained at the right level. The PCX is on the average at 32 % of the theoretical Pmax (median 29.4 %; Linf25: 23.4 %). Conclusion: These data define threshold values allowing to define a reduced ability to oxidize lipids (oxidation rate less than 140 mg/min LIPOXmax less than 22 % of the theoretical Pmax or less than 58 % of the theoretical FCmax). Thus EXCAL remains mandatory to determine these levels that are distributed over a wide range of powers and are not predictable.